The Benefit of Shift Work Schedules for Nurses’ Outcome: A Sytematic Review - Mahmud Ady Yuwanto (JENDELA NURSING JOURNAL, 2022)
Background: the nurse scheduling problem (NSP) is a serious and complex challenge in the medical industry. Effective, efficient, and high-quality services must be carried out by nurses in hospitals.Purpose: the goal of the systematic review was to find out how nurses have a positive impact on shift schedules on professional nurses in hospitals.Methods: employed the PRISMA approach. Electronic search engines from Proquest, Science Direct, and Ebsco were used to locate pertinent publications. Only English-language publications released between January 1, 2019 and December 31, 2021, had an inpatient hospital focus.Results: after identifying 265 references initially, duplicates were eliminated, and then authors from 6 pertinent papers were chosen. Overall, nurses reported that 12-hour shifts had a favorable impact on retention, including "the ability to retain experienced staff." Most nurses are flexible, don't get too tired, and will respond to patient requests like "better handoff" and "improvement of morale", Conclusion: Given that shift nurses are supposed to work about 37 hours per week and that 12-hour shifts are popular (i.e., three shifts of 12-hours). Nurse managers may think about taking action to assist nurses in reducing potential job stress brought on by the need to work shifts in order to maintain patient care. More investigation is required.